High‐grade uterine sarcoma with osteosarcomatous differentiation arising from a MED12‐mutated leiomyoma, a case report. Issue 3 (14th January 2021) - Le, Minh‐Khang; Omori, Makiko; Oishi, Naoki; Oi, Megumi; Fukasawa, Hiroko; Hirata, Shuji; Kondo, Tetsuo
Abstract : Uterine osteosarcoma has been reported, but it is an extremely rare tumor with highly aggressive behavior and poor prognosis. The pathogenesis of uterine osteosarcoma is not fully understood. Herein, we report on a high‐grade uterine sarcoma with focal osteosarcomatous differentiation that developed from a long‐standing MED12 ‐mutated leiomyoma. A 47‐year‐old nulligravida woman, with known uterine leiomyoma presented with abdominal pain and distention. Imaging analyses revealed a tumor with a large cystic area in the uterine corpus and multiple metastases in intrapelvic and paraaortic lymph nodes, left ovary and left lung. With a clinical diagnosis of uterine sarcoma the patient underwent abdominal total hysterectomy, bilateral salpingo‐oophorectomy, partial omentectomy and removal of the left obturator lymph node. Despite postoperative chemotherapy and radiation therapy, the tumor progressed rapidly. She died 18 weeks after the surgery. Histopathologic examination identified a high‐grade pleomorphic sarcoma in which focal osteoid production was observed. This high‐grade sarcoma with focal osteosarcomatous differentiation was located within the uterine leiomyoma, and Sanger sequencing showed the identical MED12 L36R mutation in both the osteosarcomatous and leiomyomatous components supporting the shared origin of these two components. We, therefore, concluded that the high‐grade sarcoma with osteosarcomatous differentiation arose from the transformation of the precedent leiomyoma.